Intra-firm coopetition in corporate groups operating in Poland - Mierzejewska, Wioletta (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
Coopetition is a combination of two dynamics: cooperation and competition. Most of the studies concerns coopetition on the inter-firm level. But coopetition appears also on the intra-firm level and manifests itself in the simultaneous cooperation and competition of departments, divisions or subsidiaries in one organization or corporate group. The paper presents the results of empirical research on intra-firm coopetition on the example of cooperation and competition between subsidiaries in corporate groups. The aim was to identify the intensity and nature of coopetition in the corporate group. The results show that coopetition in analyzed corporate groups is dominated by cooperation and occurs in all activities of the value chain, although in some it is more often indicated than in others.